2017
DOI: 10.21608/absb.2017.8163
|View full text |Cite
|
Sign up to set email alerts
|

Zoogeographical Analysis of the Egyptian Scorpion Fauna

Abstract: The geographical distribution and diversity of the scorpion fauna of Egypt was examined based on a large collection covering most of the country and in view of recent revisionary systematics. Six ecologically distinct zoogeographical regions are targeted in a collection scheme. The ecological and historical biogeography of the present-day distribution of the scorpion fauna of Egypt is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 19 publications
2
21
0
Order By: Relevance
“…Also, he found the same species at different locations in Egypt which included: Marsa Matruh, El-Dabaa, Wadi El-Natron, Wadi El Rayan, Bahariya, Faiyum, Wadi El Ranga, Bir Abraq, Abu Saafa, Abu Ramad. On the other side, Saleh et al (2017) In the present study some morphometric parameters were measured for the recorded scorpion species. Comparing the present results of the species Leiurus quinquestriatus with those measured by Lourenço et al (2006) for one male collected from Omdurman, Sudan, it could be concluded that nearly all studied morphometric parameters are the same as that measured by the above authors, where he recorded that total length = 6.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…Also, he found the same species at different locations in Egypt which included: Marsa Matruh, El-Dabaa, Wadi El-Natron, Wadi El Rayan, Bahariya, Faiyum, Wadi El Ranga, Bir Abraq, Abu Saafa, Abu Ramad. On the other side, Saleh et al (2017) In the present study some morphometric parameters were measured for the recorded scorpion species. Comparing the present results of the species Leiurus quinquestriatus with those measured by Lourenço et al (2006) for one male collected from Omdurman, Sudan, it could be concluded that nearly all studied morphometric parameters are the same as that measured by the above authors, where he recorded that total length = 6.…”
Section: Discussionmentioning
confidence: 95%
“…Also, he found the same species at different locations in Egypt which included: Siwa and Bahrain. On the other side, Saleh et al (2017) found Orthochirus innesi in the Western Mediterranean coastal desert; Western inland desert; Delta and Eastern inland desert. Badry et al (2017) recorded Buthacus leptochelys (Ehrenberg, After El-Hennawy, 1987After El-Hennawy, 1987 1828) in the New Valley at Farafra, Kharga.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The deathstalker scorpion or yellow scorpion Leiurus quinquestriatus Hemprich & Ehrenberg (Buthidae: Scorpiones: Arachnida) can be found in desert and scrubland habitats ranging from North Africa through to the Middle East. In Egypt, Saleh et al (2017) reported that two species of scorpions (Androctonus amoreuxi and L. quinquestriatus) have been recorded from six eco-geographical regions. The toxicity of venom solutions from some scorpion species was assessed against the mealworm Tenebrio molitor.…”
Section: Introductionmentioning
confidence: 99%